Stress among Medical Undergraduates after the Introduction of CBME Curriculum by NMC of a Medical College in Assam: A Cross-sectional Study - Pranjal J Chakravarty; Soumitra Ghosh; Barasha Saharia; Karuna Hazarika (Indian Journal of Private Psychiatry)
Background: Stress is an inevitable phenomenon. Medical college environment is a stressful environment due to its exhaustive academic and extracurricular activities. A competency-based medical education (CBME) curriculum was introduced in 2019. Aim: This online study was undertaken at Tezpur Medical College to explore stress among medical students from the CBME curriculum. Materials and methods: The Medical Student Stressor Questionnaire (MSSQ) tool was applied and divided into six domains. Results: A total of 400 students responded to the online study. Out of these, 185 were female and 215 were male. The students comprised a heterogeneous group from different batches ranging from 1st to 7th semesters with the 7th semester comprising the highest (29.5%) and the 1st semester as the lowest (19%). Academic-related stressors (ARS) have been associated with the highest stress (2.19 ± 0.85) and drive and desire-related stressor have the lowest stress (1.33 ± 0.94). The mean scores for males were lower than for females and were statistically significant. Both the overall score and ARS domain scores differ across semesters significantly. Comparable findings have been revealed in this study with studies from pre-CBME curriculum era. Conclusion: Stress management strategies and the provision of a congenial environment in the medical college may help to reduce stress.